2021
DOI: 10.1016/j.ajic.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus contamination of hospital-use-only mobile phones and efficacy of 222-nm ultraviolet disinfection

Abstract: Background: Mobile phones may be contaminated with nosocomial pathogens such as methicillin-resistant Staphylococcus aureus (MRSA). The aim of this study was to investigate the MRSA contamination rate on doctors' hospital-use-only mobile phones and the efficacy of 222-nm ultraviolet light (UV) disinfection. Methods: We investigated the MRSA contamination rate of doctors' hospital-use-only mobile phones, as well as the reduction in MRSA counts on plastic plates and aerobic bacteria (AB) on mobile phones before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Accordingly, differences in particle diameters can explain the different efficacies of inhibition between bacteria and phage observed in our study. Disinfection by 222‐nm UV‐C was effective for MRSA and aerobic bacteria contamination on doctors' hospital‐use‐only mobile phones (39). Our study suggested the possible inactivation efficacy for microorganisms by 222‐nm irradiation on the desk surfaces where the PC keyboards were located, the table where the slitlamp microscope was there, and the floor where the device's footswitch was there in the full‐room UVGI settings.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, differences in particle diameters can explain the different efficacies of inhibition between bacteria and phage observed in our study. Disinfection by 222‐nm UV‐C was effective for MRSA and aerobic bacteria contamination on doctors' hospital‐use‐only mobile phones (39). Our study suggested the possible inactivation efficacy for microorganisms by 222‐nm irradiation on the desk surfaces where the PC keyboards were located, the table where the slitlamp microscope was there, and the floor where the device's footswitch was there in the full‐room UVGI settings.…”
Section: Discussionmentioning
confidence: 99%
“…The Care222™ (Ushio Inc., Tokyo, Japan) UVC-emitting device used in this study was a 222 nm Kr–Cl excimer lamp module. The lamp contains an optical filter that restricted spectra-emitting light ranging between 200 and 230 nm, of which the maximum output wavelength was 222 nm [ 7 , 8 ]. To evaluate the differences in the effect of the continuous and intermittent irradiation of 222 nm UVC on SARS-CoV-2 inactivation, we experimented with 5 min of continuous and intermittent irradiation for 0.1, 0.05, 0.013 and 0.003 mW/cm 2 of 222 nm UVC.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Furthermore, studies have shown that bacteria isolated from mobile phones are MDR. 19 A study carried out in Ethiopia found an overall prevalence of 69.9% MDR bacterial isolates. 12 Consequently, contaminated mobile phones, being one of the most highly touched surfaces, act as reservoirs for organisms and may play a role in the spread of HAI caused by MDR organisms in the hospital setting and the community.…”
Section: Introductionmentioning
confidence: 99%